Perilaku Petani Terhadap Risiko Usahatani Rumput Laut di Desa Bungin Permai Kecamatan Tinanggea Kabupaten Konawe Selatan - Susanti, Fitri; Fausayana, Ine; Abdullah, Weka Gusmiarty (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This research was conducted in the Bungin Permai Village of Tinanggea Sub-district of Konawe Selatan District. The aims of this research were: (1) to know the behavior of farmers toward the risk of farming, and (2) to know the socio-economic factors that affect the behavior of farmers toward the risk of farming seaweed. Sample farmer determined using simple random sampling methods. The number of samples in this research as much as 37 seaweed farmers. Analytical techniques used in this research is twofold, namely the utility function kuadratik to analyze the behavior of farmers against risks, and multiple linear regression analysis was used to analyse the socio-economic factors that affect the behavior of farmers toward the risk. The results of the analysis show that the behavior of farmers towards risks are risk averse 86.48% of farmers, risk lovers 5.41% of farmers, and risk neutral 8.11% of farmers. The experience of farming and extensive construction will increase the reluctance of farmers toward the risk, while the acceptance will increase farmers courage toward the risk of farming